PENGARUH MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA KELAS IV SEKLAH DASAR NEGERI 58 DESA TELUK MAJELIS - Fatiha; Mislan; Fitri Nauli Siagian (STKIP Subang, 2024)
experimental class and class IV as the control class. The data collection techniques in this research were critical thinking ability tests, interviews and documentation This research is a quantitative experimental research with a Quasi Experimental Design design which aims to determine the effect of the problem based learning model to improve students' critical thinking skills in solving mathematics story problems in class IV of the 58th state elementary school in Teluk Majaelis village. The sample used in this research was class IV students at 58 Teluk Majlis Elementary School with a sampling technique using a saturated sampling technique with class IV as the. Data analysis used in this research is normality test, homogeneity test and hypothesis test. The results of the research conducted show that the problem based learning model has an effect in improving students' critical thinking abilities in solving mathematics story problems in class IV of the 58 Teluk Majlis State Elementary School which can be seen from the average score in the class that uses the problem based learning model, namely from 54, 00 becomes 76.41 With a significant value of Sig=0.000, which is a significant value smaller than 0.05 (p<0.05), then if a comparison of tcount and ttable is carried out in this study it can be determined using the t distribution table at a significance of 0 .05 or 0.025 (two-sided test) with df = n-2 or df = (17 + 15) - 2 = 30, we get a ttable of 2.042. With the test criteria tcount > from ttable or 8.162 > 2.042 at significance level (a) 5%. Keywords: Problem Based Learning Model, Critical Thinking Skills